Draft Genomes and Comparative Analysis of Seven Mangrove Rhizosphere-Associated Fungi Isolated From Kandelia obovata and Acanthus ilicifolius - Shi, Chengcheng; Chen, Jianwei; Ge, Qijin; Sun, Jiahui; Guo, Wenjie; Wang, Jie; Peng, Ling; Xu, Qiwu; Fan, Guangyi; Zhang, Wenwei; Liu, Xin (Frontiers in Fungal Biology, 2021)
Mangroves are one of the most productive and biologically diverse ecosystems, with unique plants, animals and microorganisms adapted to the harsh coastal environments. Although fungi are widely distributed in the mangrove ecosystem and they are playing an important role in the decomposition of organic matter, their genomic profiles are still poorly understood. In this study, we isolated seven Ascomycota fungi (Westerdykella dispersa F012, Trichoderma lixii F014, Aspergillus tubingensis F023, Penicillium brefeldianum F032, Neoroussoella solani F033, Talaromyces fuscoviridis F034 and Arthrinium marii F035) from rhizospheres of two mangroves of Kandelia obovata and Acanthus ilicifolius. We sequenced and assembled the whole genome of these fungi, resulting in size ranging from 29Mb to 48Mb, while contig N50 from 112Kb to 833Kb. We generated six novel fungi genomes except A. tubingensis, and the gene completeness and genome completeness of all seven genomes are higher than 94%. Comparing with non-mangrove fungi, we found Carbohydrate-Binding Modules (CBM32), a subfamily of carbohydrate active enzymes, only detected in two mangrove fungi. Another two subfamilies, Glycoside Hydrolases (GH6) and Polysaccharide Lyases (PL4), were significantly different in gene copy number between Kandelia obovata and Acanthus ilicifolius rhizospheres (P-value 0.041 for GH6, 0.047 for PL4). These findings may indicate an important influence of mangrove environments or hosts on the ability of decomposition in rhizosphere fungi. Secondary metabolite biosynthesis gene clusters were detected and we found the mangrove fungi averagely contain 18 Type I Polyketide synthase, which was significantly higher than 13 in non-mangrove fungi (P-value 0.048), suggesting their potential roles in producing bioactive compounds that important for fungi development and ecology. We reported seven mangrove-associated fungal genomes in this study and compared their carbohydrate active enzymes and secondary metabolites genes with those of non-mangrove fungi, and the results suggest that there are differences in genetic information among fungi in different habitats.